Determining the Performance Measurement of SME from Economic Value Added: Study on Hungary, Somogy County - Devesh Singh; Zoltan Gal; Raqif Huseynov; Michał Wojtaszek (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
EVA (Economic Value Added) permits commercial businesses to figure out whether the business is operating in profit and the money can be put into effect into a more profitable source. A leading EVA is a sign that the company has a greater value. The goal of this study is to identify if SMEs' actions carried out on a daily basis are able to generate economic value added for their business. The study is based on a comparative study between Hungary and 28 EU countries. The study is carried out in Hungary’s region of Somogy county. First, the variables for research were created and research was carried out at ground level. The research used the Expletory Factor analysis method to find EVA determinants. The results showed that determinants work together to reshape the regional industrial growth. The research demonstrated that finance and sluggish production are the major determinants in Somogy county. Entrepreneurs' skills and finance have the major impact, which means that to achieve a high growth in SMEs, policy makers have to solve these two problems and make the policy concentric toward finance and high skill development problem.